To frame or not to frame? Cone‐beam CT‐based analysis of head immobilization devices specific to linac‐based stereotactic radiosurgery and radiotherapy. (24th January 2018) - Babic, Steven; Lee, Young; Ruschin, Mark; Lochray, Fiona; Lightstone, Alex; Atenafu, Eshetu; Phan, Nic; Mainprize, Todd; Tsao, May; Soliman, Hany; Sahgal, Arjun
Abstract: Purpose: Noninvasive frameless systems are increasingly being utilized for head immobilization in stereotactic radiosurgery (SRS). Knowing the head positioning reproducibility of frameless systems and their respective ability to limit intrafractional head motion is important in order to safely perform SRS. The purpose of this study was to evaluate and compare the intrafractional head motion of an invasive frame and a series of frameless systems for single fraction SRS and fractionated/hypofractionated stereotactic radiotherapy (FSRT/HF‐SRT). Methods: The noninvasive PinPoint system was used on 15 HF‐SRT and 21 SRS patients. Intrafractional motion for these patients was compared to 15 SRS patients immobilized with Cosman‐Roberts‐Wells (CRW) frame, and a FSRT population that respectively included 23, 32, and 15 patients immobilized using Gill‐Thomas‐Cosman (GTC) frame, Uniframe, and Orfit. All HF‐SRT and FSRT patients were treated using intensity‐modulated radiation therapy on a linear accelerator equipped with cone‐beam CT (CBCT) and a robotic couch. SRS patients were treated using gantry‐mounted stereotactic cones. The CBCT image‐guidance protocol included initial setup, pretreatment and post‐treatment verification images. The residual error determined from the post‐treatment CBCT was used as a surrogate for intrafractional head motion during treatment. Results: The mean intrafractional motion over all fractions with PinPoint was 0.62 ± 0.33 mm and 0.45 ± 0.33 mm, respectively, for the HF‐SRT and SRS cohort of patients ( P ‐value = 0.266). For CRW, GTC, Orfit, and Uniframe, the mean intrafractional motions were 0.30 ± 0.21 mm, 0.54 ± 0.76 mm, 0.73 ± 0.49 mm, and 0.76 ± 0.51 mm, respectively. For CRW, PinPoint, GTC, Orfit, and Uniframe, intrafractional motion exceeded 1.5 mm in 0%, 0%, 5%, 6%, and 8% of all fractions treated, respectively. Conclusions: The noninvasive PinPoint system and the invasive CRW frame stringently limit cranial intrafractional motion, while the latter provides superior immobilization. Based on the results of this study, our clinical practice for malignant tumors has evolved to apply an invasive CRW frame only for metastases in eloquent locations to minimize normal tissue exposure.